Cover Image, Volume 2, Number 1, March 2020. Issue 1 (19th March 2020) - Or, Tyler; Gourley, Storm W. D.; Kaliyappan, Karthikeyan; Yu, Aiping; Chen, Zhongwei
Abstract : The recycling of lithium‐ion batteries addresses concerns over waste accumulation and the depletion of critical mineral resources associated with their large‐scale production and application. In article number 10.1002/cey2.29, Tyler Or, Storm Gourley, Karthikeyan Kaliyappan, Aiping Yu, and Zhongwei Chen review new recycling methods for cathodes comprising a mixed‐metal composition in the context of meeting demands for the growing electric vehicle market.